Osteogenic Differentiation and Proliferation of Apical Papilla Stem Cells Using Chitosan-Coated Nanohydroxyapatite and Bioactive Glass Nanoparticles - Elshahat, Sara; Elgendy, Abeer Abdelhakim; Elsewify, Tarek (European Journal of Dentistry, 2024)
Objective The aim of this study was to evaluate the osteogenic differentiation ability and proliferation of apical papilla stem cells (SCAPs) using chitosan-coated nanohydroxyapatite and bioactive glass nanoparticles.Materials and Methods Hydroxyapatite, chitosan-coated nanohydroxyapatite, and bioactive glass 45S5 nanoparticles were prepared and characterized using a transmission electron microscope and X-ray diffraction. SCAPs were harvested from freshly extracted impacted wisdom teeth, cultured, and characterized using flow cytometric analysis. Tested nanomaterials were mixed and samples were classified into five equal groups as follows: negative control group: SCAP with Dulbecco's modified eagle's medium, positive control group: SCAP with inductive media, first experimental group: nanohydroxyapatite with SCAP, second experimental group: chitosan-coated nanohydroxyapatite with SCAP, third experimental group: bioactive glass nanoparticles with SCAP. Osteoblastic differentiation was assessed using an alkaline phosphatase (ALP) assay. Receptor activator of nuclear factor kappa beta ligand (RANKL) expression was evaluated using specific polyclonal antibodies by fluorescence microscope. The proliferation of SCAP was assessed using cell count and viability of trypan blue in addition to an 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay.Results Isolated SCAP showed a nonhematopoietic origin. Chitosan-coated nanohydroxyapatite showed the highest ALP concentration followed by nanobioactive glass, nanohydroxyapatite, and negative control. Chitosan-coated nanohydroxyapatite showed the highest H score followed by nanobioactive glass, nanohydroxyapatite, and negative control in RANKL expression. Chitosan-coated nanohydroxyapatite showed the highest viable cell count.Conclusion SCAP isolation is achievable from extracted fully impacted immature third molars. All tested biomaterials have the ability to induce osteogenic differentiation and proliferation of SCAP. Composite nanoparticle materials show better osteogenic differentiation and proliferation of SCAP than single nanoparticles.
Keywords: osteoinduction; osteoconduction; regenerative endodontic